2022
DOI: 10.1093/mtomcs/mfac076
|View full text |Cite
|
Sign up to set email alerts
|

Imaging zinc trafficking in vivo by positron emission tomography with zinc-62

Abstract: Non-invasive imaging techniques to dynamically map whole-body trafficking of essential metals in vivo in health and diseases are needed. Despite 62 Zn having appropriate physical properties for PET imaging (half-life, 9.3 h; positron emission, 8.2%), its complex decay via 62Cu (half-life, 10 min; positron emission, 97%) has limited its use. We aimed to develop a method to extract 62 Zn from a 62 Zn/62Cu generator, and to investigate its use for in vivo imaging of zinc trafficking despite its complex decay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Therefore, the impact of the R138X variant on global zinc trafficking was also studied. PET images revealed the typical biodistribution for 62 Zn and 63 Zn as seen in previous studies in mice and humans (7,10,11), including uptake in the heart, liver, kidneys, pancreas, intestines, and salivary glands (Figure 1A). PET quantification in all three groups revealed that 62 Zn is rapidly cleared within minutes from the blood following i.v.…”
Section: Kinetic Delivery Of Zinc From Blood To Tissues Over 1 H Rema...supporting
confidence: 73%
See 2 more Smart Citations
“…Therefore, the impact of the R138X variant on global zinc trafficking was also studied. PET images revealed the typical biodistribution for 62 Zn and 63 Zn as seen in previous studies in mice and humans (7,10,11), including uptake in the heart, liver, kidneys, pancreas, intestines, and salivary glands (Figure 1A). PET quantification in all three groups revealed that 62 Zn is rapidly cleared within minutes from the blood following i.v.…”
Section: Kinetic Delivery Of Zinc From Blood To Tissues Over 1 H Rema...supporting
confidence: 73%
“…[ 62 Zn]Zn-citrate was produced as previously described (7). In brief, this was achieved by proton irradiation (27 MeV,35 µA for 9 h) of a copper foil target that was subsequently dissolved in concentrated hydrochloric acid and hydrogen peroxide.…”
Section: Production Of 62 Zn For Pet Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…General Information Zinc (Zn) exists in three positron-emitting isotopes ( 62/63/65 Zn) that have the potential to be used as PET biomarkers of zinc trafficking in various pathological conditions [182]. Among them, 62 Zn has limited use because it decays to another positron-emitting isotope, 62 Cu (β + = 98%; t 1/2 = 9.7 min), which could confound the image interpretation of PET scans [182]. Nevertheless, 62 Zn has been used preclinically to image zinc transport in pancreatic exocrine function [183].…”
Section: Production and Availabilitymentioning
confidence: 99%
“…Among the Zn PET isotopes, 65 Zn has the longest half-life (t 1/2 = 243.9 d), making it unsuitable for diagnostic imaging because it will cause high radiation exposure to patients over time [182]. 63 Zn has a favorable decay characteristic (β + = 93%; t 1/2 = 38.47 min) for diagnostic imaging and pharmacokinetic studies [184,185].…”
Section: Production and Availabilitymentioning
confidence: 99%